**(C) is correct option**

Dark Mode

12 votes

Best answer

Following two K-Maps are equivalent and represent the same boolean function.

While the first K-Map gives us the boolean expression in Sum-of-Product form, and the second K-Map gives us the same boolean function in Product-of-Sum form:

**(C) is correct option!**

PS: If SOP is asked answer will be (A).

3 votes

Or Use the K-map get the Min terms s we get in this question.#USING MIN-TERMS and convert them to MAX term Check for Options

as in using K map we get

F= D'B + B'D (Is would be easy till this part)

Now apply de-morgan's law

F'= (D + B') (D'+B)

solve this we get

F'= DD' +DB + D'B' BB'

Apply de-morgan's again

F'' = (D'+B')(D+B)

as in using K map we get

F= D'B + B'D (Is would be easy till this part)

Now apply de-morgan's law

F'= (D + B') (D'+B)

solve this we get

F'= DD' +DB + D'B' BB'

Apply de-morgan's again

F'' = (D'+B')(D+B)